Influence of Journal Bearing Axial Grooves on the Dynamic Behavior of Horizontal Rotors - Miguel Angelo de Carvalho Michalski; Moysés Zindeluk; Renato de Oliveira Rocha (Shock and Vibration)
Journal bearing design and the lubricant characteristics are very influential in a rotating machine behaviour. The bearing geometry can drastically affect the lubricant flow and also the rotor dynamics. Approaching that issue, this paper presents an experimental study of the dynamic behavior of a horizontal rotor suported by journal bearings with semi-circular axial grooves. The journal bearings were manufactured with a varied number of axial grooves and a versatile test rig is used, making possible the analysis of different configurations. The acquired signals are analyzed with classical and non-linear tools and the differences among the rotors’ configurations can be shown.